2022
DOI: 10.1101/2022.08.26.505400
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alcohol dependence modifies brain networks activated during abstinence and reaccess: a c-fos-based analysis in mice

Abstract: High-level alcohol consumption causes neuroplastic changes in the brain that lead to negative affective and somatic symptoms when alcohol is withdrawn, promoting relapse drinking. We have some understanding of these plastic changes in defined brain circuits and cell types, but unbiased approaches are needed to explore broader patterns of adaptations. Here, we employed whole-brain c-fos mapping and network analysis to assess how brain-wide patterns of neuronal activity are altered during acute alcohol abstinenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Changes in the patterns of neuronal coreactivity, also called the functional connectome, can be observed in humans and rodents during withdrawal from nicotine (Hobkirk et al, 2018;Cheng et al, 2019;Kimbrough et al, 2021). Whole-brain imaging with single-cell resolution using light-sheet microscopy on cleared brains (Renier et al, 2014(Renier et al, , 2016Ueda et al, 2020) has made the study of brain-wide functional networks at single-cell resolution possible by looking at the expression of the immediate-early gene Fos (Wheeler et al, 2013;Vetere et al, 2017;Kimbrough et al, 2020;Smith et al, 2021;Roland et al, 2022), a marker of neuronal reactivity, which integrates neuronal activation during a period of 1-2 h, an ideal temporal window to characterize nicotine withdrawal. Using this approach, we have found that mice in withdrawal exhibit a pronounced increase in coactivation patterns throughout the brain (Kimbrough et al, 2020(Kimbrough et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the patterns of neuronal coreactivity, also called the functional connectome, can be observed in humans and rodents during withdrawal from nicotine (Hobkirk et al, 2018;Cheng et al, 2019;Kimbrough et al, 2021). Whole-brain imaging with single-cell resolution using light-sheet microscopy on cleared brains (Renier et al, 2014(Renier et al, , 2016Ueda et al, 2020) has made the study of brain-wide functional networks at single-cell resolution possible by looking at the expression of the immediate-early gene Fos (Wheeler et al, 2013;Vetere et al, 2017;Kimbrough et al, 2020;Smith et al, 2021;Roland et al, 2022), a marker of neuronal reactivity, which integrates neuronal activation during a period of 1-2 h, an ideal temporal window to characterize nicotine withdrawal. Using this approach, we have found that mice in withdrawal exhibit a pronounced increase in coactivation patterns throughout the brain (Kimbrough et al, 2020(Kimbrough et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%